Investigação das propriedades mecânicas e adesão interfacial dos compósitos de polipropileno virgem e reciclado reforçados com fibras e microfibras de bambu - Melo, Santino Loruan Silvestre de (2016)
The development of renewable and biodegradable materials is undoubtedly one of the most important of research to reduce environmental impacts. Therefore, the development of materials that can replace the use of materials from fossil fuels with raw material biodegradable, and almost unlimited achievement, makes plant fibers are a promising reinforcement to non-biodegradable materials. In this study, bamboo fibers were used to reinforce composites. In order to improve the fiber / matrix adhesion, chemical modifications were made on the fiber surface. Bamboo microfibers were also found to produce micro-composites and evaluate the mechanical stability of these modified micro-composites, which has the advantage of orientation in all directions of the material. The mechanical properties of mercerized and acetylated fibers and their composites with virgin and recycled polypropylene were obtained to analyze the stress at break and elastic modulus were affected after the surface treatment applied to the fiber. Analyses by SEM revealed the degradation of fibers depending on chemical modification, indicating the phase-matrix adhesion of composites and micro-composites. The FTIR fibers showed the efficacy of mercerization and acetylation surface with the appearance / disappearance of bands in the range of 3300 cm-1-3700 cm-1 and also at 1750 cm-1. With fiber tensile tests, it could be seen as chemical procedures affect the mechanical stability of the fibers. X-ray diffraction (XRD) were used to verify the degree of crystallinity of the fibers and relate it to their final mechanical properties. The crystallinity index with increased NaOH concentration (in mercerising solution) and decreased over time with acetylation. Tensile tests of fibers and composites revealed the influence of chemical modifications on the fibers. When For a higher concentration of NaOH in solution, the fibers had a higher maximum stress at rupture. However, for a longer acetylation was lower maximum stress at rupture of those fibers. For the virgin polypropylene composites uni- and bidirectional caused mechanical reinforcement fibers in some guidelines, such as the one-way 0 °. In all composites with recycled matrix, the fibers have been proven effective in the mechanical reinforcement of composites, reinforcing the maximum stress at break of up to 350% for composites bi-directional fibers. The modification procedure by acetylation in composites was effective as the mechanical reinforcement compared to composites with only mercerized fibers.